Comparing the effectiveness of two interventional methods; lecture-based versus self-learning; on mothers' ability to assess the development of 12-month-old children seeking comprehensive health services centers - Maryam Mohammadi; Zahra Judaki; Ali Ramezankhani; Soheila Khodkarim; Seyed Hamed Barekati (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Developmental delay of children is a global health concern. One of the important measures in the care of children and the assessment of children's health is the knowledge and ability of mothers about the condition of their children's development. The purpose of this study was to compare the outcome of lecture-based method versus self-learning package on the ability of mothers to assess the development of their 12-month-old children seeking comprehensive health services centers in Arak city, central province of Iran. MATERIALS AND METHODS: The present study is a semi-experimental study. The sample included 189 mothers of 12-month-old children. The data gathering tools were age and stages questionnaire with confirmed validity and reliability. The participants in the study were divided into three group as follows: lecture, self-learning, and control group which were evaluated by pretest and posttest. Data analysis was performed with SPSS version 21. RESULTS: The results of this study indicate that both of interventional methods; lectures and self-learning; had a statistically significant effect on the ability of mothers to evaluate the development of their children (P = 0.001). In the self-learning group, the score of the participants increased from 53.35 ± 44.269 to 70.15 ± 47.290 and in the lecture group, the score of participants increased from 55.28 ± 41.268 to 16.14 ± 38.292 according to the posttests. CONCLUSION: Due to the importance of self-care and active role in the learning process, we suggest the use of self-learning package in practice.